AST-to-Platelet Ratio Index as Potential Early-Warning Biomarker for Sepsis-Associated Liver Injury in Children: A Database Study - Dou, Jiaying; Zhou, Yiping; Cui, Yun; Chen, Min; Wang, Chunxia; Zhang, Yucai (Frontiers in Pediatrics, 2019)
Background: Sepsis-associated liver injury (SALI) is a risk factor of poor outcome in patients with sepsis. The early warning biomarkers for identifying SALI remain poorly defined. Aims: To identify the potential predictors of occurrence of SALI in pediatric patients with sepsis. Methods: We retrospectively analyzed the sepsis database based on the medical records of patients admitted to the pediatric intensive care unit (PICU) in Shanghai Children’s Hospital from July 2014 to June 2018. Patients’ demographics, co-morbidities and laboratory variables were collected. Univariate and multivariate logistic analysis were used to explore risk factors of SALI, and receiver operating characteristic (ROC) curve analysis was used to evaluate their predictive significances for SALI occurrence. Results: Of 1,645 eligible patients, 1147 patients were included, and 105 cases had SALI. The indexes including AST-to-platelet ratio index (APRI), γ-GT and lactate dehydrogenase (LDH) were independent risk factors for SALI. Moreover, APRI was powerful to predict SALI in children (AUC: 0.889, 95% CI：0.851 - 0.927) with a sensitivity of 84.6 % and a specificity of 84.3 % at the cutoff point of 0.340. APRI was superior to LDH and not inferior to γ-GT for predicting SALI. Conclusion: APRI is an independent risk factor of SALI occurrence, and elevated APRI within 24h after PICU admission (> 0.340) is a potential predictor for SALI in children.